2022
DOI: 10.4102/aej.v10i1.623
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to embedding indigenous knowledge systems in Made in Africa Evaluations

Abstract: Background: In this article, the authors make a case for weaving indigenous knowledge systems (IKS) with monitoring and evaluation of interventions targeted at communities on the African continent. Current efforts do not make explicit reference to indigenous knowledge in Made in Africa Evaluation (MAE). Indigenous knowledge systems are implied as the defining aspect of MAE, being called upon to be fused with existing evaluation systems and practices in order to enhance evaluation in African communities.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Culturally evaluative ideas have the potential to shape evaluation theory and practice in Africa, judging from recent CRE studies (Chirau & Ramasobana 2022;Mapitsa & Ngwato 2020;Pophiwa & Saidi 2022). Contemporary evaluation notions seem to push CRE values, knowledge, ideals, and other cultural realities on a modernisation guilt path where cultural evaluative values and philosophies tend to be deemed anachronistic in evaluation research and practice.…”
Section: Indigenously or Culturally Responsive Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…Culturally evaluative ideas have the potential to shape evaluation theory and practice in Africa, judging from recent CRE studies (Chirau & Ramasobana 2022;Mapitsa & Ngwato 2020;Pophiwa & Saidi 2022). Contemporary evaluation notions seem to push CRE values, knowledge, ideals, and other cultural realities on a modernisation guilt path where cultural evaluative values and philosophies tend to be deemed anachronistic in evaluation research and practice.…”
Section: Indigenously or Culturally Responsive Evaluationmentioning
confidence: 99%
“…Nonetheless, the recent quest among African evaluators is to ensure that the evaluation research and practices are rooted in 'cultural competence, contextual relevance and cultural validity' (Pophiwa & Saidi 2022). The notion is that this will guarantee sustainability because Euro-American evaluation approaches have failed to properly measure the programme outcome and reverse developmental challenges in the continent (Chilisa & Mertens 2021).…”
Section: Empirical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study found that there is considerable scope for the evaluation sector to draw on indigenous knowledge systems research, particularly drawing on process and methodological lessons from designing studies, as well as defining power dynamics and critical systems approaches. The article by Pophiwa and Saidi (2022) shares approaches to embedding indigenous knowledge systems in MAEs. The aim and objective are to call for the enrichment of MAE in setting the agenda and bringing agency to evaluation practices in Africa against centuries of unsustainable developmental practices that continue to underdevelop the continent.…”
Section: Read Onlinementioning
confidence: 99%